2004
DOI: 10.1111/j.1464-410x.2003.04773.x
|View full text |Cite
|
Sign up to set email alerts
|

Topical anaesthetic use for treating premature ejaculation: a double‐blind, randomized, placebo‐controlled study

Abstract: OBJECTIVE To assess the use of a topical anaesthetic mixture to improve premature ejaculation (PE), for which penile hypersensitivity might be a cause. PATIENTS AND METHODS The study included 42 men divided in two groups; group A used a lidocaine‐prilocaine solution and group B used an inert cream. The tubes of cream were distributed randomly and participants asked to note any unpleasant symptoms, difficulties and the results of each attempt at intercourse, assessed by the intravaginal ejaculatory latency time… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
101
0
4

Year Published

2006
2006
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 159 publications
(109 citation statements)
references
References 22 publications
3
101
0
4
Order By: Relevance
“…In one RCT, numbers withdrawing were imbalanced across groups [placebo 44%, Eutectic Mixture of Local Anaesthetics (EMLA), 28%] and data were analysed per-protocol (withdrawals exclude). 19 One reported that 30% of participants withdrew overall but did not reported how many withdrew by treatment group. 21 Both RCTs were considered to be at an overall high risk due to attrition bias.…”
Section: Risk Of Bias Assessment Of Rctsmentioning
confidence: 99%
See 3 more Smart Citations
“…In one RCT, numbers withdrawing were imbalanced across groups [placebo 44%, Eutectic Mixture of Local Anaesthetics (EMLA), 28%] and data were analysed per-protocol (withdrawals exclude). 19 One reported that 30% of participants withdrew overall but did not reported how many withdrew by treatment group. 21 Both RCTs were considered to be at an overall high risk due to attrition bias.…”
Section: Risk Of Bias Assessment Of Rctsmentioning
confidence: 99%
“…Only one RCT reported that a random sequence generation method, 18 and only one reported that treatment allocation was concealed. 19 One RCT prescribed either an oral or a topical treatment to treatment groups and as such, participants and caregivers would not have been blinded. 20…”
Section: Risk Of Bias Assessment Of Rctsmentioning
confidence: 99%
See 2 more Smart Citations
“…73 Another placebo-controlled study reported the optimal application time to be 20 min prior to intercourse. 74 Lidocaine spray.…”
Section: A1-adrenoceptor Antagonistmentioning
confidence: 99%